AVALIAÇÃO CLÍNICA DA EFETIVIDADE E DA SENSIBILIDADE AO CLAREAMENTO DENTAL EM PACIENTES COM RESTAURAÇÕES ESTÉTICAS - Bonafé, Elize Tatiane Ribeiro (2012)
Dental bleaching in patients with esthetic restoration is a clinical reality, but there are no studies assessing its effectiveness and post-operative sensitivity. The aim of this study was to evaluate the effectiveness of a bleaching agent and the sensitivity associated to dental bleaching in patients with esthetic restorations. Sixty patients were selected and divided in 2 groups: H (patients with no restoration) and R (patients with esthetic restoration). The groups H and R were allocated into subgroups depending on the prior application of a desensitizing agent (D - with desensitizing; S - without desensitizing), resulting in four subgroups: HS, HD, RS and RD. It was performed two sessions of three applications of 15 minutes each with 35% hydrogen peroxide for all the patients. The color was assessed by the visual scale and a spectrophotometer prior to bleaching, one week after the each session and six months after the end of the treatment. The patients recorded their sensitivity perception on a NRS scale immediately after bleaching and up to 7 days after each session. The bleaching effectiveness was evaluated at each recall by one way ANOVA and Tukey’s tests (α=0.05). The percentage of patients with dental sensitivity was evaluated by Fisher’s Exact Test and intensity differences among groups were compared with Mann-Whitney U test (α=0.05). The results showed a high prevalence of sensitivity associated to dental bleaching. The sensitivity rate was higher for the groups with esthetic restoration but the application of a desensitizing agent significantly decreased the intensity of sensitivity in all groups (p<0,05). It was noted the same effectiveness of bleaching for all the groups and in the 6-month evaluation it was found color stability. It was concluded that patients with aesthetic restorations did not have higher prevalence of sensitivity associated to dental bleaching, however, its intensity was greater. The application of a desensitizing agent decreased the sensitivity intensity in patients with and without esthetic restorations.